The Relationship of Self-Efficacy with Pandemic Burnout on Nurses in Bali - Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi; Ketut Lisna Wati (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Health workers, especially nurses, are at the forefront of fighting Covid-19. Nurses carrying out their duties during a pandemic are vulnerable to experiencing pandemic burnout. The impact of the burnout pandemic will cause a decrease in service quality. Nurses carrying out their responsibilities during the Covid-19 pandemic require self-efficacy in their abilities. Self-efficacy is a person's belief that he can master the situation and produce something positive. Objective: This study aims to determine the relationship between self-efficacy and nurses' pandemic burnout in Bali. Method: This research was quantitative with a non-probability sampling design and a cross-sectional approach. Total sampling was used with a total sample of 103 respondents. Result: The majority nurses have high self-efficacy 49 people (47.6%) and low pandemic burnout 48 people (46.6%). The Spearman rank correlation test showed that the p-value = 0.000 with a correlation strength value of 0.537 had a negative correlation direction. Conclusion: it can be concluded that the higher the self-efficacy, the lower the nurse's pandemic burnout. Nurses who have good self-efficacy tend to experience low pandemic burnout. Self-efficacy will help nurses to survive in the face of obstacles and unpleasant experiences, especially during the current pandemic. Keywords: Pandemic burnout; self-efficacy; Nurses